2011
DOI: 10.1159/000324157
|View full text |Cite
|
Sign up to set email alerts
|

Do Bicarbonate-Based Solutions for Continuous Renal Replacement Therapy Offer Better Control of Metabolic Acidosis than Lactate-Containing Fluids?

Abstract: Introduction: Evidence that bicarbonate haemofiltration and dialysate fluids are superior to lactate in patients with acute kidney injury treated by continuous renal replacement therapy (CRRT) remains controversial. Methods: We prospectively audited acid-base during the first 48 h of CRRT in 62 patients, using bicarbonate and lactate fluids. Results: Baseline lactate was greater in the bicarbonate group (4.76 ± 0.77 vs. 2.92 ± 0.5 mmol/l, p < 0.01), but pH, bicarbonate, chloride and base excess were similar. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Regarding the dialysate and haemofiltration fluid, a recent study showed that bicarbonate fluids led to a more rapid fall in lactate and greater improvement in base excess during CRRT, but not to an overall improvement in the control of acidosis (Agarwal et al . ). As a consequence, the use of bicarbonate buffer is now preferred.…”
Section: Section 10: Management Of Severe Malariamentioning
confidence: 97%
“…Regarding the dialysate and haemofiltration fluid, a recent study showed that bicarbonate fluids led to a more rapid fall in lactate and greater improvement in base excess during CRRT, but not to an overall improvement in the control of acidosis (Agarwal et al . ). As a consequence, the use of bicarbonate buffer is now preferred.…”
Section: Section 10: Management Of Severe Malariamentioning
confidence: 97%
“…Rationale: Intermittent hemodialysis was recommended as the first-line initial ECTR by the workgroup because it is superior in terms of its correction of acidemia and removal of metformin and lactic acid (144). Bicarbonate-based dialysate buffers are standard today and are preferable to acetate-based buffers that fail to correct serum bicarbonate as quickly (226,227); replacement or dialysate solutions containing lactate may delay correction of hyperlactatemia (211,(228)(229)(230). Bicarbonate-based dialysate buffers are standard today and are preferable to acetate-based buffers that fail to correct serum bicarbonate as quickly (226,227); replacement or dialysate solutions containing lactate may delay correction of hyperlactatemia (211,(228)(229)(230).…”
Section: Choice Of Ectrmentioning
confidence: 99%
“…Lactate has an additional inconvenience since high replacement doses or impaired liver function may cause hyperlactatemia. The latter is not harmful in the absence of metabolic acidosis but may necessitate a switch to bicarbonate because failure to correct acidosis has been demonstrated in up to 13% of patients [22]. Studies of hepatic clearance using indocyanine green showed that hyperlactatemia related to lactate replacement fluid can unmask liver dysfunction.…”
Section: Adverse Events Related To Rrtmentioning
confidence: 99%